CIDERA JANJI (WANPRESTASI) DALAM PERJANJIAN FIDUSIA BERDASARKAN PASAL 15 AYAT (3) UU NOMOR 42 TAHUN 1999 PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR: 18/PUU-XVII/2019 - Nugraha, Sigit Nurhadi (AL WASATH Jurnal Ilmu Hukum, 2021)
Verdict of Constitution Court Number 18/PUU-XVII/2019 makes a new reinterpretation to â€œbreach of contractâ€ or â€œdefaultâ€ based on article 15 paragraph (3) of Law Number 42 Year 1999 concerning Fidusiary Guarantee (hereinafter referred to â€œUU Nomor 42 Tahun 1999â€). Before the existence of this Constitution Courtâ€™s verdict, statement of â€œbreach of contractâ€ or â€œdefaultâ€always be maked by creditor (as financing company) by his own opinion. This condition makes the creditor tend to act arbitrarily to the debtor which is in a weaker position. After the existence of constitution courtâ€™s verdict number 18/PUU-XVII/2019, â€œbreach of contractâ€ or â€œdefaultâ€ of the debtor must be determined based on the agreement between creditor dan debtor or it can be determined based on particular legal action, thatâ€™s by litigation procedure on court institution. This makes kreditor unable to to act arbitrarily anymore in determining of the debtorâ€™s default.